الرضا الوظيفي وأثره في أداء معلمي مدارس التعليم الأساسي في محافظة جنوب الشرقية في سلطنة عمان - راسبي، سالمة هلال ناصر (Kulliyah of Education, International Islamic University Malaysia, 2021)
This research aimed to identify the effect of job satisfaction on the job performance of school primary teachers in South Sharqiyah, Sultanate of Oman. The research used the correlational descriptive research method. The population of the research consisted of all primary school teachers in South sharqiyah, and the research sample included (370) male and female teachers. In order to achieve the objectives of the research, a questionnaire was developed and its validity and reliability were verified. The descriptive and inferential statistics and multiple regression were used to analyze the collected data. The analyses showed that the level of job performance of primary school teachers in South sharqiyah, was high, with Mean score (4.11), while the job satisfaction of teachers was moderate, with Mean score (3.12). The findings also showed that there were statistically significant differences in the means scores for four dimensions of job satisfaction by gender, p < 0.05 in favour of female teachers with Means range (3.21-3.97). There was also a statistically significant effect for relationship with management, relationship with colleagues at work, opportunities for promotion, and opportunities for growth) on job performance, p < 0.05. The research recommends to those in charge of education and its development to award teachers their promotions in accordance with the existing laws and regulations, give teachers monetary incentives, increase salaries, and to involve teachers in the decision making process. The research also recommends to researchers carrying out further studies on the current job satisfaction in educational institutions, and employing modern techniques to collect feedback on the teachers' skills and level of job performance regularly.